Upaya Orang Tua dalam Memotivasi Kesungguhan Belajar Anak di Desa Bulusari Tarokan Kabupaten Kediri - Doni Saputra (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
This research is in the background by the importance of parents' role as the first and foremost educator for the child to motivate their children in order to increase the seriousness of learning. When children learn should always get attention and guidance from parents. Parents must meet the children's learning needs and always give motivation, otherwise it will be difficult to familiarize the child to learn this research using a qualitative approach that has the characteristics of: natural background And researchers as a key source, and research is descriptive. The results of the study after the analysis, namely: (1) Children's study pattern at home in Bulusari village, Tarokan District of Kediri regency of each child varies, some who like learning in a quiet or silent condition, some are happy to learn While watching TV or listening to the song. Children's learning patterns in this village use two approaches that are self-learning (individual) and with teachers looking for tutoring and learning guidance. (2) The motivational forms of the family so that the children learn vigorous is to give examples to the child, because the child has the data to emulate the good. (3) Forms of motivation given by parents to foster children's learning spirit is to provide complete learning facilities, giving gifts or rewards, creating conducive atmosphere and learning conditions so that children can learn and punishment for a child who does not want to learn and lazy to learn and the child who dropped his learning achievement.